2020
DOI: 10.1111/ejn.14915
|View full text |Cite
|
Sign up to set email alerts
|

Dim light at night exacerbates stroke outcome

Abstract: Circadian rhythms are endogenous biological cycles that synchronize physiology and behaviour to promote optimal function. These ~24‐hr internal rhythms are set to precisely 24 hr daily by exposure to the sun. However, the prevalence of night‐time lighting has the potential to dysregulate these biological functions. Hospital patients may be particularly vulnerable to the consequences of light at night because of their compromised physiological state. A mouse model of stroke (middle cerebral artery occlusion; MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
1
14
3
Order By: Relevance
“…Our study confirms that there is less damage if the TBI occurs during hours of activity, which could be regardless of the type of injury (model used). In rodents with CNS injuries, less damage has been reported in the dark phase of the cycle (Beker et al., 2018; Schallner et al., 2017), and more significant damage or less recovery owing to circadian desynchronization due to the presence of dim or continuous light (Beker et al., 2018; Earnest et al., 2016; Fonken et al., 2019; Ramsey et al., 2020; Weil et al., 2020). There has been little research on TBI and its relationship to diurnal variation (Estrada‐Rojo et al., 2018b; Martinez‐Tapia et al., 2020b; Martinez‐Vargas et al., 2006, 2013) or circadian disruption (Li et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirms that there is less damage if the TBI occurs during hours of activity, which could be regardless of the type of injury (model used). In rodents with CNS injuries, less damage has been reported in the dark phase of the cycle (Beker et al., 2018; Schallner et al., 2017), and more significant damage or less recovery owing to circadian desynchronization due to the presence of dim or continuous light (Beker et al., 2018; Earnest et al., 2016; Fonken et al., 2019; Ramsey et al., 2020; Weil et al., 2020). There has been little research on TBI and its relationship to diurnal variation (Estrada‐Rojo et al., 2018b; Martinez‐Tapia et al., 2020b; Martinez‐Vargas et al., 2006, 2013) or circadian disruption (Li et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our central hypothesis—that dLAN would exacerbate post-SCI symptoms and recovery outcomes—was prompted by a pair of studies that explored similar questions in mouse models of global cerebral ischemia and ischemic stroke (Fonken et al, 2019; Weil et al, 2020). In both studies, housing mice in dLAN post-operation resulted in increased neuronal cell death accompanied by the upregulation of pro-inflammatory factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Upon neuronal injury, heightened immune activation is observed during the morning increasing the risk for neurocytoxicity and secondary damage compared to the evening. In addition, disruptions to circadian rhythms and core clock gene function through exposure to light at night disrupts immune function and increases neuroinflammation ( Walker et al, 2020 ), that has been corroborated in an ischemic murine model in which 24 h of exposure to dLAN post stroke increased pro-inflammatory response (TNF-α, IL-6, and IL-1) in the ipsilateral cortex that can further amplify secondary damage of the infarct ( Weil et al, 2020 ). Disruptions to circadian rhythms can lead to a prothrombotic state, in which patients during the morning time point are especially at risk for poor outcome, further highlighting the importance of time of day when considering therapeutic strategies.…”
Section: Molecular Clock’s Influence On Cardiovascular Cerebrovascular and Immune Parametersmentioning
confidence: 95%
“…In addition to disruption of circadian rhythms by repeated phase shifts (jet lag), foundational science research has examined the role of circadian disruption by light at night in stroke outcome. Studies evaluating the impact of ecologically relevant levels of dLAN (5 lux) have reported that stroke lesion size was significantly larger in dLAN mice compared to mice housed in dark nights after 24 h ( Weil et al, 2020 ). Furthermore, this study reported that mice exposed to three days of dLAN post MCAO increased TNF-α, IL-6, and IL-1 in the ipsilateral hemisphere of the brain, and displayed increased anxiety-like behavior compared to control mice ( Weil et al, 2020 ).…”
Section: Time Of Day Alterations On Ischemic Stroke Outcome (Basic Science)mentioning
confidence: 99%
See 1 more Smart Citation